2020
DOI: 10.1140/epjc/s10052-020-7826-9
|View full text |Cite
|
Sign up to set email alerts
|

Fermion and graviton in Dirac–Born–Infeld braneworld models

Abstract: In this paper, we study the braneworld models with non-standard kinetic term of Dirac-Born-Infeld (DBI) type in two case which are (I) in usual gravity and (II) in f (T) gravity. In each of these cases, we examine gravity localization on branes and show that both models are stable and capable of gravity localizing in a similar manner to the standard case of braneworld models. In addition, we investigate the problem of fermion localization in both models and by considering the Yukawa coupling as a function of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…This means that the Cuscuton dynamics also plays a role in this case, contributing to change the geometry of the brane, an issue that may modify phenomenological aspects of particle physics in the F(R)+T scenario. This motivates other investigations, in particular, on the entrapment of fermions [48][49][50]. Moreover, it may also contribute to change the cosmological behavior under possible braneworld cosmology scenarios; see, e.g., Refs.…”
Section: Comments and Conclusionmentioning
confidence: 59%
“…This means that the Cuscuton dynamics also plays a role in this case, contributing to change the geometry of the brane, an issue that may modify phenomenological aspects of particle physics in the F(R)+T scenario. This motivates other investigations, in particular, on the entrapment of fermions [48][49][50]. Moreover, it may also contribute to change the cosmological behavior under possible braneworld cosmology scenarios; see, e.g., Refs.…”
Section: Comments and Conclusionmentioning
confidence: 59%
“…However, there are significant differences between them. For a spinor field, the left and right components of the zero mode can not been localized on brane at the same time [15,16,25,[30][31][32][33][34][35]. If we regard the zero mode particle as an electron, a contradiction would arise since it has been observed that electrons have both chiralities.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This mechanism is called as localization. There are a lot of references for the thick brane models and localization of gravity and matter fields [7][8][9][10][11][12][13][14][15][16][17][18][19][20], see Refs. [21][22][23][24][25][26] for reviews.…”
Section: Introductionmentioning
confidence: 99%
“…This has been considered in several different contexts in Refs. [35][36][37][38][39][40][41][42][43][44][45][46][47][48] and in references therein. In particular, an interesting scenario arises for the construction of braneworld solutions in modified gravity with Lagrange multipliers [47,48].…”
Section: Introductionmentioning
confidence: 99%